A pilot case crossover study of the use of padded headgear in junior Australian football - Catherine Willmott; Jonathan Reyes; Jack VK Nguyen; Andrew McIntosh; Jennifer Makovec-Knight; Michael Makdissi; Patrick Clifton; Peter Harcourt; Biswadev Mitra (Concussion)
Aim: To explore soft-shell padded headgear (HG) use, player behavior and injuries associated with HG in junior Australian football. Methods: Prospective case-crossover with head impact measurement,...